Direito fundamental à segurança pública: poder soberano, doutrina do inimigo e estado de exceção - Lorenzoni, Lara Ferreira (2024)
Public security is a fundamental right enshrined in the Federal Constitution of 1988, considered a duty of the state, a right and responsibility of all. Despite this, the way in which this prerogative is materialized in Brazil, with frequent police operations and massacres, as well as other violations of fundamental rights and guarantees, leads to the question of how much this provision is being operationalized within the interpretative-constitutional dictates. Brazilian doctrine, representing the theoretical common sense of jurists, is more often than not silent on the subject and, when it does speak out, refers to the state of nature of bestial men who need to be controlled by a strong centralized apparatus - the Leviathan. This leads to the research problem: what are the remnants of Hobbes' contract theory with regard to legal understanding and the realization of the fundamental right to public security in the Brazil? How could this give rise to a permanent state of exception in Brazil in the field of security? By hypothesis, we admit that the the control of violence with a constitutional basis in public security, exercised fundamentally by the penal apparatus, is closer to the Hobbesian Leviathan, implacable (and unquestionable) against its enemies, than it is to democracy. It seems that, in the name of security, people are killed, watched, imprisoned unduly, devices that ensure due process of law are removed, in short, a state of constant abnormality is established. What's more, this could be in line with Giorgio Agamben's theory of the state of exception, in which the extermination camp would be the modern paradigm par excellence. For this reason, the theoretical framework chosen for the analysis is Agamben's category of state of exception. The archaeological method is chosen, in an exercise of "excavation" in search of the unspoken and neutralized about the fundamental right to public safety, that is, its philosophical matrices. In the course of these chapters, we follow the path of contract theory, with security replacing the divine origin of power and the complete capture of biological and individual life by the sovereign. This is reflected in the theories of Hobbes, John Locke and Jean-Jacques Rousseau. Next, facts relevant to this study about the transition from the Military Dictatorship to the New Republic are recounted. This period was marked by agreements and accommodations with the previous occupants of power, projecting the racist-inquisitorial soul of highly militarized public 11 security into the democratic regime, a moment that coincided with the arrival of capitalism in its most predatory and terrifying version, neoliberalism. Capitalism without factories has an extremely limited housing plan for misery: death and prison. The exception here, in the wake of Giorgio Agamben, is permanent - naked lives (killable bodies) prevail. This time, the enemy to be slaughtered is embodied in the young black man from the periphery, reduced to the category of Homo Sacer, like in Brazil at the end of the century: the drug trafficker. Hobbes' old fear is the affection mobilized to legitimize the sprawl of the extermination camp, the piling up of bodies, the hatred of life shared in plurality, in short, the annihilation of democracy